2020 42nd Annual International Conference of the IEEE Engineering in Medicine &Amp; Biology Society (EMBC) 2020
DOI: 10.1109/embc44109.2020.9176841
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing acoustic and prosodic fluctuations in free speech to predict psychosis onset in high-risk youths

Abstract: The diagnosis and treatment of psychiatric disorders depends on the analysis of behavior through language by a clinical specialist. This analysis is subjective in nature and could benefit from automated, objective acoustic and linguistic processing methods. This integrated approach would convey a richer representation of patient speech, particularly for expression of emotion. In this work, we explore the potential of acoustic and prosodic metrics to infer clinical variables and predict psychosis, a condition w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 20 publications
0
23
2
Order By: Relevance
“…Second, speech disturbances are closely related to important predictors for clinical endpoints. Abnormalities in pausing have been associated with positive and negative symptoms, in both individuals at clinical high risk (Agurto et al, 2020; Sichlinger et al, 2019; Stanislawski et al, 2021) and patients with schizophrenia (Cohen et al, 2016). In addition, speech disturbances are related to cognitive function (Barker et al, 2020; R.…”
mentioning
confidence: 99%
“…Second, speech disturbances are closely related to important predictors for clinical endpoints. Abnormalities in pausing have been associated with positive and negative symptoms, in both individuals at clinical high risk (Agurto et al, 2020; Sichlinger et al, 2019; Stanislawski et al, 2021) and patients with schizophrenia (Cohen et al, 2016). In addition, speech disturbances are related to cognitive function (Barker et al, 2020; R.…”
mentioning
confidence: 99%
“…The strength of the LMBAS is that it is a theoretically-driven, knowledge-based system that allows users to evaluate the link between speech production and perception. For future work, the performance of LMBAS can be compared to the performance of other acoustic features commonly extracted for use in voice quality analysis, and other neuropsychiatric disorders that commonly affect voice and emotion recognition (Aguiar et al, 2019; Agurto et al, 2019; Agurto et al, 2020; Bone et al, 2017; Cummins et al, 2015; Deshpande et al, 2020; Eyben et al, 2010; Harati et al, 2018; Huang et al, 2018; Konig et al, 2015; Low et al, 2020; Maor et al, 2020; Marmar et al, 2019; Norel et al, 2018; Orozco-Arroyave et al, 2016; Perez et al, 2018; Pinkas et al, 2020; Rusz et al, 2011; Sara et al, 2020). Some of these features include autocorrelation, zero crossing rate, entropy/entropy ratios across targeted spectral ranges, energy/intensity, Mel/Bark Frequency Cepstral Coefficients (MFCC), linear predictive coefficients (LPC), perceptual linear predictive coefficients (PLP), perceptual linear predictive Cepstral Coefficients (PLP-CC), spectral features, psychoacoustic sharpness, spectral harmonicity, F0, F0 Harmonics ratios, jitter/shimmer, and a variety of statistical and mathematical summary measurements for these frame-level values.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study found that acoustic features were associated with negative symptoms in CHR‐P participants (Stanislawski et al, 2021). Our study and Sichlinger et al (2019) elicited speech from clinical interviews, whilst Agurto et al (2020) and Stanislawski et al (2021) employed open‐ended interviews. The different acquisition protocols might explain the divergent findings, given that the context and content of interview settings significantly influence speech parameters (Cohen et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The features extracted were grouped into temporal (de Boer et al, 2020) and prosodic (Agurto et al, 2020) measures.…”
Section: Speech Acquisitionmentioning
confidence: 99%